Travestis, escolas e processos de subjetivação - Peres, Wiliam Siqueira [UNESP] (My University, 2010)
In this paper, we analyze transvestites’ reports regarding their experiences at schools. It is a cartography that focuses on negative and positive aspects which call to consideration difficulties from the operators of the education in dealing with this population. Such cartography clarifies the urgent need for opening to a broaden debate to increase the educational actions in the perspective of the protection of the Sexual and Human Rights with strategies of inclusion and defense of citizenship. In spite of the transvestites’ difficulties in enduring and concluding their studies, it is possible to locate some schools in which the transvestites can be welcomed and respected in consideration to their personal choices. Thus, it clarifies the lines that composes their subjectivation processes.

Neste artigo colocamos em análise relatos de travestis a respeito de suas experiências com o sistema de ensino brasileiro. Trata-se de uma cartografia que coloca em questão aspectos negativos e positivos que denunciam dificuldades por parte dos operadores da educação no trato com essa população, o que clarifica a urgente necessidade de abertura de um debate maior que amplie as ações educativas em uma perspectiva da defesa dos direitos sexuais e humanos, estratégias de inclusão e defesa da cidadania. Apesar das dificuldades das travestis em permanecer e concluir seus estudos, é possível localizar alguns operadores da educação e suas escolas em que as mesmas possam se sentir acolhidas e respeitadas diante de suas escolhas pessoais, clarificando sobre as linhas que compõe os processos de subjetivação.
Transvestites, educational system and subjectivation processes
Keywords: Transvestites; Schools; Stigma; Subjectivation processes; Travestis; Escolas; Estigmas; Processos de Subjetivação